The Eastern Partnership Initiative After the Vilnius Summit (November 28-29, 2013) - K. Petrov (Международная аналитика)
A crisis of EU eastern policy was shown by Vilnius summit. However, the EU remains consistent in its efforts to giving the EU institutions the nature of the framework for all multilateral agreements within the framework of the initiative «Eastern Partnership». It should not be understand as the weakening of the program, but its further focusing and concentration. This article make predictions about the allocation of a number of countries (Moldova, Georgia) in a separate sub-block for which the integration will be accelerated, while others experience a slowdown in program participants. Relations between EU and Ukraine and between EU and Belarus are purely political and will be less dependent on the implementation of the «Eastern Partnership».